Aerodynamics of modern soccer balls - Oggiano, L.; Saetran, L. (Procedia Engineering, 2010)
The scope of this article is to find out what are the differences between four modern soccer balls and find out how these differences influences the flight path of the ball in a free kick. Experiments have been carried out in static and spinning conditions and drag and side forces have been acquired. The results from the wind tunnel experiments have been implemented in a Matlab routine and a free kick simulation using the different balls has been made. The effect of the different balls on the flight path has been calculated. Major differences between the different soccer balls have been found.